Single filament mechanical characterisation of hemp fibres for reinforcing composite materials - Cristina Romão (2003)
The work described in this paper refers to the mechanical characterisation ofPortuguese natural hemp fibres, for the utilisation on the production of compositematerials with an epoxy matrix.A single filament mechanical characterisation is made, for fibres with and without acleaning bath from a solution of sodium hydroxide, with the propose of increasing theadherence fibre/matrix.